2009
DOI: 10.1063/1.3263151
|View full text |Cite
|
Sign up to set email alerts
|

Homologous temperature dependence of global surface scaling behaviors of polycrystalline copper films

Abstract: A strategy integrating structure zone model with dynamic scaling theory was proposed to study the global surface dynamics of polycrystalline Cu films deposited at different homologous temperature Ts/Tm. The evolution of roughness exponent α and growth exponent β reveals a transition from random deposition to surface diffusion dominated smoothening in the lower Ts/Tm regime and then to rapid surface roughening in the higher Ts/Tm regime. In contrast to that of amorphous films, the distinct scaling behavior in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, in recent years, many experimental and theoretical studies have reported scaling patterns very different from that predicted by the Eq. (2) 11 12 13 14 15 16 17 18 19 20 21 22 . In such cases, growth models with different exponents at long (global/saturated) and short (local) length scales have been suggested.…”
mentioning
confidence: 99%
“…However, in recent years, many experimental and theoretical studies have reported scaling patterns very different from that predicted by the Eq. (2) 11 12 13 14 15 16 17 18 19 20 21 22 . In such cases, growth models with different exponents at long (global/saturated) and short (local) length scales have been suggested.…”
mentioning
confidence: 99%
“…Additional support can be found in an early study on sputtered Cu films. 27 Based on the above analysis, we conclude that the sublayer surface roughening of all HM W films originates from the limited surface diffusion mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In our case, substrate rotation excludes the self-shadowing effect. 27 The independence of phase structure on P m also excluded the influence of preferred grain growth or film texture. 28 Additionally, the Schwoebel effect seems only to matter in single-crystalline films, therefore it could be negligible in our polycrystalline system.…”
Section: Resultsmentioning
confidence: 99%
“…The shape and structure are extremely susceptible to the temperature of the substrate. [10][11][12][13][14][15][16][17][18] Bi is a metal with a low melting point (T m = 544.45 K), and its properties are particularly affected by the temperature used during preparation. Different deposition methods have been used to prepare and analyze the effects of substrate temperature on Bi films, such as pulsed laser deposition, magnetron sputtering, and thermal evaporation.…”
Section: Introductionmentioning
confidence: 99%